Using Small Group Duscussion as Part of Problem Based Learning in Teaching Speaking Skill for ESP Students - Martriwati Martriwati; Burhayani Burhayani (UICELL, 2022)
Using small group discussion as teaching method has been widely used by teachers but study about the use of small group discussion as part of Problem Based Learning in teaching speaking for ESP students in Indonesia context is quite limited found. Seeing the lack of the research the writer conducted it which has the aim to examine the effectiveness of using Small Group Discussion in teaching speaking skill for ESP students at UHAMKA. The research method used in this research was pre-experimental research. The sample was taken from the third students of Cardiovascular Engineering and Pre-test as well as Post-test were given to that class. The findings indicated t-is 9.69 and t- is 1.70, it means the Null Hypothesis ( is rejected and is accepted. In conclusion the Small Group Discussion as part of PBL is effective in teaching speaking skill for ESP students. Keywords: Problem based learning, Group discussion, ESP